Evaluasi Kinerja Pegawai di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu Kabupaten Minahasa - Mantiri, Jeane; Walangitan, Brigita; Bura, Arnold; Polii, E. H. (Academy of Education Journal, 2024)
This research is aimed at identifying, describing and analyzing the performance evaluation of officers in the Capital Plantation and Integrated Services Department of One Door Minahasa Cabinet. This research uses qualitative descriptive methods. Data is collected through observation techniques, interviews and interviews, documentation. The results of this study, showing the quality of the work of the staff in the license area, is still less related to the standards of work applied by the office not fully implemented by the existing staff, such as operating computers or mastering IT. The still poor work culture also greatly affects the performance of the existing staff. And there are barriers that affect the quality of the performance of officials, that is, the limitation of resources and supplies that are still lacking and the minimum budget of the licensing field.